High-altitude immune remodeling in children with Mycoplasma pneumoniae pneumonia: a multi-center transcriptome study - Luo, Yingying; Hou, Jing; Lu, Weifen; Cao, Haixia; Hao, Erwa; Zhang, Yaogang; Liu, Feng; Zhu, Yifan; Ma, Yanyan (Frontiers in Immunology, 2025)
IntroductionA global outbreak of Mycoplasma pneumoniae pneumonia (MPP) emerged following the Corona Virus Disease 2019 (COVID-19) pandemic. Different altitudes significantly impact community-acquired pneumonia (CAP). Whether there are differences in the immune responses of children with MPP at different altitudes is unknown.MethodsThis study collected bronchoalveolar lavage fluid (BALF) from children with MPP in Nanjing (altitude, 20 m) or Qinghai (altitude, 4,058.40 m) for transcriptome sequencing analysis to investigate pulmonary immune responses in children with MPP at different altitudes.ResultsChildren with refractory Mycoplasma pneumoniae pneumonia (RMPP) in the plateau group showed milder clinical manifestations, with shorter duration of fever before admission, lower levels of serum tissue injury markers, and lower incidences of atelectasis. Neutrophils and T cells in the lungs of the plain group were activated, along with the activation of the NOD-like receptor signaling pathway or the inhibition of the PI3K–Akt signaling pathway. The immune cells of children with MPP in the plateau group showed adaptive changes, which manifested as increased M2 polarization of macrophages, CD8+ T cells, and B cells, and decreased neutrophils and CD4+ T cells.ConclusionExcessive activation of the pulmonary immune response in children with MPP of the plain region may be related to the NOD-like receptor signaling pathway and PI3K–Akt signaling pathway. Adaptive changes in immune cells occurred in children with MPP of the plateau region.